Balloon Pulmonary Angioplasty in Heterozygous RNF213 p.Arg4810Lys Variant Carriers Diagnosed With Chronic Thromboembolic Pulmonary Hypertension - Takatoyo Kiko; Ryotaro Asano; Tomohiko Ishibashi; Hiroyuki Endo; Shinya Fujisaki; Ryo Takano; Mitsumasa Akao; Naruhiro Nishi; Hiroya Hayashi; Akiyuki Kotoku; Hiroki Horinouchi; Jin Ueda; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The heterozygous ring finger protein 213 (RNF213) p.Arg4810Lys variant has been identified in patients with chronic thromboembolic pulmonary hypertension (CTEPH). This study aimed to clarify the influence of the RNF213 p.Arg4810Lys variant on the response to balloon pulmonary angioplasty (BPA) in patients with CTEPH. Methods We retrospectively analyzed 93 patients with CTEPH who underwent BPA by analyzing the RNF213 p.Arg4810Lys variant. Clinical parameters and hemodynamics following BPA were compared between RNF213 p.Arg4810Lys variant carriers and noncarriers, along with BPA‐related complications. Results Among 93 patients, 7 (8%) were heterozygous RNF213 p.Arg4810Lys variant carriers and 86 (92%) were noncarriers. Both groups showed significant improvements in mean pulmonary artery pressure and pulmonary vascular resistance following BPA. However, the 6‐minute walk distance, symptoms, cardiac index, and right ventricular function did not significantly improve in heterozygous RNF213 variant carriers, whereas noncarriers showed notable improvements. Group differences in mean change from baseline to follow‐up were significant in cardiac index (0.4 L/min per m2 [95% CI, 0.1–0.8]; P=0.019), 6‐minute walk distance (70 m [95% CI, 6–135]; P=0.036), and right ventricular ejection fraction (9% [95% CI, 5–12]; P<0.001), all favoring noncarriers. Of the 515 BPA procedures, complications were significantly higher in variant carriers than in noncarriers (25% versus 8%; P<0.001). Multivariate logistic regression analysis indicated a significant association between the RNF213 p.Arg4810Lys variant and BPA complications (adjusted odds ratio, 7.0 [95% CI, 1.1–44.4]; P=0.038). Conclusions Heterozygous RNF213 p.Arg4810Lys variant carriers exhibited a poor response to BPA, suggesting that the RNF213 p.Arg4810Lys variant could be a risk factor for BPA complications.